Directed Transport of a Short Polymer Chain on a Temperature-Dependent Ratchet Potential (Contemporary Mathematics, 2025)
We investigate the transport properties of a single flexible polymer chain moving along a periodic ratchet potential modulated by a spatially varying temperature. At steady state, the polymer exhibits rapid unidirectional motion, with the efficiency of current rectification strongly influenced by its elasticity and size. Analytical and numerical analyses demonstrate that the steady-state transport can be effectively regulated by modulating the elastic constant. Notably, the stall force, at which the polymer current ceases, remains independent of both chain length and coupling strength. Beyond the stall force, the polymer's mobility exhibits a strong dependence on its flexibility and size. These results highlight a tunable mechanism for controlling polymer transport, offering potential applications in directed polymer motion and the sorting of multicomponent systems based on intrinsic material properties.
Keywords: polymer transport; ratchet potential; temperature gradient; stochastic dynamics; elastic coupling